Bulletproof investing gaining financial control in uncertain times - Fitzgerald, James (John Wiley & Sons, Inc., 2021)
Take the reins of your financial future with this powerful and insightful new resource In Bulletproof Investing, real estate expert, investor, entrepreneur, and author James Fitzgerald, delivers a collection of personal stories and experiences that will show how you too can gain and retain financial control of your life. You'll learn how to spend less than you earn, find a mentor, identify a purpose for your financial wellbeing, and, ultimately, learn to achieve financial independence. This important book shows you how to: Improve your mental health by removing the stress and anxiety of financial insecurity Familiarise yourself with the right tools to control your financial destiny Minimise and manage risk, rather than trying fruitlessly to eliminate it Take advantage of the miracle of compound growth and watch your investment portfolio flourish Stop working hard and start working smart, letting your money do much of the work for you Perfect for millennials, adults with children, and those nearing retirement aiming for financial control and stability, Bulletproof Investing will also earn a place in the libraries of anyone hoping to gain a firmer grasp of their financial reality and investment portfolio.